Evaluation and Management of Caustic Injuries from Ingestion of Acid or Alkaline Substances - Park, Kyung Sik (Clinical endoscopy, 2014)
Although the numbers have decreased compared with in the past, cases of patients who ingest caustic substances and visit the emergency room are not rare. However, well-summarized data about caustic injuries are insufficient. Therefore, in this article, I will discuss the etiologic causative agents, injury mechanism, and clinical characteristics, as well as the endoscopic evaluation of the degree of injury and proper management of the patient, in gastrointestinal caustic injury.